Enhanced magneto-optical activity of multilayer thin films: a novel platform for magnetic nanoparticle sensing - DEĞER, CANER (IOP PUBLISHING LTD, 2020)
In this study, we present a novel platform based on the measurement of magneto-optic Kerr effect of a magnetic multilayer thin film sensor with perpendicular magnetic anisotropy, to achieve the quantitative analysis of magnetic nanoparticles (MNPs). Microliter droplets include a varied amount of MNPs located on the sensor surface to perform a systematic investigation of sensing mechanisms. The interaction between the sensor and MNPs, which must be well understood to enhance the sensitivity, is investigated through experiments and micromagnetic simulations. The simulations, in accordance with the experiments, allow us to extract the detection limit of our sensor. We anticipate that our study provides a rational basis for highly sensitive, single-use and precise sensing of MNPs, and will influence future discussions on MNP-magnetic thin film interactions.
Keywords: perpendicular magnetic anisotropy; magnetic nanoparticles; magnetic sensor; magneto-optic Kerr effect; OSCILLATORY INTERLAYER EXCHANGE; ANISOTROPY; MAGNETORESISTANCE; SENSORS